Perlindungan Hukum Terhadap Hak Atas Pendidikan Anak Miskin Di Kabupaten Karangasem - Sugita, I Made; Sri Ratmini, Ni Ketut; Wardhani, Ida Ayu Sri Kusuma; Ariani, Ni Putu (Jayapangus Press, 2024)
The right to education for poor children is one of the rights that must be protected by a state to achieve the broadest possible welfare of the people without discrimination. Karangasem Regency is one of the districts in Bali Province with the highest number of poor people, which has an impact on the large number of children dropping out of school and resulting in poor children's right to education in Karangasem Regency not being properly obtained. The aim of this research is to determine and analyze legal protection for the right to education of poor children in Karangasem Regency. The type of research used in compiling this research is empirical legal research. This research is descriptive-qualitative in nature with data collection techniques, namely through observation, interviews and documentation. The results of this research indicate that legal protection for the right to education of poor children in Karangasem Regency has not been fully implemented properly. This can be seen from the dissemination of policies issued by the government to help the education of poor children in Karangasem Regency which is still not evenly distributed, and the amount of assistance provided by the government to help with the costs of educating poor children in Karangasem Regency is still limited. The obstacles faced in providing legal protection for poor children's right to education in Karangasem Regency originate from 3 factors, the first is from community factors, namely regarding community motivation in continuing education which is still low. The two factors are facilities and infrastructure, namely the number of educational facilities in the form of the number of schools, the ratio of students and teachers is still not optimal. Lastly, there is the government factor, where the validity of data on poor residents or children in Karangasem Regency is not yet optimal, which results in the legal protection being provided not being optimal.